Analisis Perceived Ease of Use dan Perceived Usefulness Pada Aplikasi PLN Mobile: Studi Kasus Pada PT PLN (Persero) UP3 Nias - Erniati Nduru; Lie Othman (Pusat Riset dan Inovasi Nasional, 2026)
Electricity is a fundamental need in modern society and plays a crucial role in supporting national development. As part of its digital transformation, PT PLN (Persero) launched the PLN Mobile application to facilitate customers in accessing electricity services independently. However, the utilization rate of this application within the UP3 Nias area remains low, despite a relatively high number of registered users. This condition indicates a gap between technological availability and user adoption. This study aims to analyze users’ perceptions of the perceived ease of use and perceived usefulness of the PLN Mobile application at PT PLN (Persero) UP3 Nias. The research employed a descriptive qualitative approach through in-depth interviews with key informants and active users. The findings reveal that PLN Mobile is generally perceived as easy to learn and operate, particularly among users familiar with digital technology, while users with lower digital literacy still encounter difficulties. In terms of usefulness, the application is considered beneficial as it improves time efficiency, transaction convenience, and service transparency. Nevertheless, limited internet infrastructure and low digital literacy remain significant barriers. This study emphasizes the importance of ease of use and perceived usefulness in shaping technology acceptance for public services and suggests enhancing digital infrastructure and continuous education to optimize PLN Mobile utilization in UP3 Nias